Performance of geotextile as a filter for drainage system - Mohd Amirul Hafiz Ilias (School of Environmental Engineering, University Malaysia Perlis, 2012)
Geotextile is very important in engineering field. In this case study, nonwoven geotextile used in the drainage system that acts as a filter. Purpose of this study was to determine the function of nonwoven geotextile as filter media and identify the quality of the filtered water for the drainage system. Therefore, the model is designed to show the filtering process. Two models are created, where a model using nonwoven geotextile type and another model which does not use a geotextile which aims to show the difference. Tank size 350 mm x 200 mm x 240 mm is used for placing material such as nonwoven geotextile, sand, soil, and aggregates which form in three layers. Based on the JKR Manual On Pavement Design, a minimum thickness for soil and aggregate is 100mm and each layer is compacted. However, the actual thickness is not used for the purpose of the model is to show the filtering process and the functions of nonwoven geotextile. Only one parameter are used, is from drainage water. After testing, the results of the water sample will be tested in terms of level of turbidity and suspended solids contained in the water. From the results show that the use of nonwoven geotextile in drainage systems have a positive impact to reduce the level of water pollution.